Measuring Overhead of Concurrency and Virtual Memory - Yauhen Klimiankou (Моделирование и анализ информационных систем)
We present the methodology, as well as results of measurements and evaluation of overhead created by concurrency and virtual memory. A special measurement technique and testbed were used to obtain the most accurate data from the experiments. This technique is focused on the measurements of the overall performance degradation that is introduced by concurrency in the form of lightweight user-level threads on IA-32 processors. We have obtained and compared results of the experiments in an environment with and without enabled virtual memory to understand what loss of performance is caused by virtual memory in itself, and how it affects the overhead associated with concurrency. The results showed that overhead of concurrency outweighs virtual memory overhead and that there is a complex dependency between them. The article is published in the author’s wording.